SCREENING FOR TUBERCULOSIS DISEASE AMONG CHILDREN: A SYSTEMATIC REVIEW - Pasande, Ratih (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction : One of the top 10 causes of death worldwide is tuberculosis (TB). An estimated 10 million new cases of TB, including 1.2 million in children, were reported in 2019. Due to the symptoms of pediatric tuberculosis (TB) being similar to those of other juvenile illnesses and the difficulty in obtaining lung samples due to children's propensity to swallow sputum, diagnosing pediatric TB is challenging. Methods : This systematic review's objective was to find reliable screening techniques for paediatric tuberculosis diagnosis. The Cochrane Central Register of Controlled Trials, ScienceDirect, PubMed, and Web of Science databases were all searched in accordance with PRISMA standards.The words "screening" and "(Tuberculosis) OR (TB) OR (TB)" and "(Children")" were used. Result : This investigation covered a total of five studies. TST and IGRA are recommended by the Food and Drug Administration (FDA) and the Centers for Disease Control and Prevention (CDC) as techniques for diagnosing M. tuberculosis infection, with certain preferences and considerations. For testing children younger than 5 years old, TST is preferred over IGRA. Conclusion :Testing BCG recipients (either as a therapy or a vaccine) or patients with subpar TST findings is preferred to be done with IGRAs.